Global research development of chondrosarcoma from 2003 to 2022: a bibliometric analysis - Duan, Hansong; Li, Jiatong; Ma, Jianfei; Chen, Ting; Zhang, He; Shang, Guanning (Frontiers in Pharmacology, 2024)
Background Chondrosarcomas are common primary malignant bone tumors; however, comprehensive bibliometric analysis in this field has not yet been conducted. Therefore, this study aimed to explore the research hotspots and trends in the field of chondrosarcoma through bibliometric analysis to help researchers understand the current status and direction of research in the field. Methods Articles and reviews related to chondrosarcoma published between 2003 and 2022 were retrieved from the Web of Science. Countries, institutions, authors, journals, references, and keywords in this field were visualized and analyzed using CtieSpace and VOSviewer software. Results Between 2003 and 2022, 4,149 relevant articles were found. The number of articles published on chondrosarcoma has increased significantly annually, mainly from 569 institutions in China and the United States, and 81 in other countries. In total, 904 authors participated in the publication of studies related to chondrosarcomas. Over the past 20 years, articles on chondrosarcoma have been published in 958 academic journals, with Skeletal Radiology having the highest number of publications. Furthermore, keywords such as “gene expression,” “radiotherapy,” “experience,” and “apoptosis” have been popular in recent years. Conclusion Over the past 20 years, the global trend in chondrosarcoma research has primarily been clinical research, with basic research as a supplement. In the future, communication and exchange between countries and institutions should be strengthened. Further, the future main research hotspots in the field of chondrosarcoma include mutated genes and signaling pathways, precision surgical treatment, proton therapy, radiation therapy, chemotherapy, immunotherapy, and other aspects.